Given that

Initial speed of the three heeler, u = 36 km/h = 36 * \frac{1000}{60*60} = 10 m/s

Final velocity of the three wheeler, v = 0

Time taken t = 4.0 seconds

Mass of the three wheeler, M = 400 kg

Mass of the driver, m = 65 kg

Total mass of the system = M + m = 400kg + 65 kg = 465 kg

Step 1: Finding the acceleration of the system

From the first equation of motion

Final velocity v = u + at

Acceleration a = \frac{v - u }{t}

a = \frac{0 - 10}{4}

a = - 2.5

Acceleration of the three-wheeler a = - 2.5 m/s^2

Step 2: Compute the vehicle's retarding force using Newton's motion equations.

According to the newton's second law of motion

Retarding force F = ma

F = 65 *- 2.5

F = 1162.5 N

he direction of force and the direction of motion are always opposing each other, hence the retarding force is always negative.

F = -1162.5 N

Hence, Average retarding force F = -1162.5 N